Experimental Aspects Suggesting a “Fluxus” of Information in the Virions of Herpes Simplex Virus Populations - Scolaro, Luis A.; Roldan, Julieta S.; Theaux, Clara; Damonte, Elsa B.; Carlucci, Maria J. (Frontiers in Microbiology, 2017)
Our perspective on nature has changed throughout history and at the same time has affected directly or indirectly our perception of biological processes. In that sense, the “fluxus” of information in a viral population arises a result of a much more complex process than the encoding of a protein by a gene, but as the consequence of the interaction between all the components of the genome and its products: DNA, RNA and proteins and its modulation by the environment. Even modest “agents of life” like viruses display an intricate way to express their information. This conclusion can be withdrawn from the huge quantity of data furnished by new and potent technologies available now to analyze viral populations. Based on this premise, evolutive processes for viruses are now interpreted as a simultaneous and coordinated phenomenon that leads to global (ie, not gradual or 'random') remodeling of the population. Our system of study involves the modulation of herpes simplex virus populations through the selective pressure exerted by carrageenans, natural compounds that intefere with virion attachment to cells. On this line, we demonstrated that the passaging of virus in the presence of carrageenans leads to the appearance of progeny virus phenotipically different from the parental seed, particularly, the emergence of syncytial (syn) variants. This event preeceds the emergence of mutations in the population which can be readily detected five passages after from the moment of the appearance of syn virus. This observation can be explained taking into consideration that the onset of phenotypic